Overview of chitosan-based nanosystems for prostate cancer therapy. (5th November 2021) - de Araújo, Jennifer Thayanne Cavalcante; Tavares Junior, Alberto Gomes; Di Filippo, Leonardo Delello; Duarte, Jonatas Lobato; Ribeiro, Tais de Cássia; Chorilli, Marlus
Graphical abstract: Abstract: Prostate cancer is considered a non-cutaneous cancer and has high prevalence and mortality rates worldwide. Chemotherapeutic agents have several side effects due to non-specific systemic biodistribution. Alternatively, nanocarriers can be an interesting strategy to overcome the limitations and undesirable consequences of conventional treatments. This review aims to explore the properties of chitosan, as well as its pharmaceutical applications in drug delivery nanosystems as a carrier or as a surface moiety for prostate cancer-targeted treatment. The chitosan-based polymeric nanosystems demonstrated good results regarding the delivery of anticancer drugs, improving their release, reducing toxicity, and promoting specific delivery to the tumor cells of prostate cancer.